Rancang Bangun Alat Monitoring dan Pengatur Suhu Air berbasis IoT - Sasongko, Amirul Akbar; Suwardono, Agus; Indrawati, Elsanda Merita; Puspitasari, M. Dewi Manikta (Universitas Nusantara PGRI Kediri, 2025)
Controlling the temperature of pond water is an important factor in cultivating gourami fish, because inappropriate temperatures can cause stress and make fish susceptible to disease. Temperatures that are too high or too low can disrupt fish metabolism, slow growth, and even cause death. This study aims to design and build an IoT-based water temperature monitoring and regulation tool in gourami fish ponds. This tool is expected to make it easier for farmers to monitor and regulate pond water temperature automatically and in real-time via a website, thereby reducing the risk of disease in gourami fish. The research methods used include hardware and software design, temperature sensor testing, and implementation of an IoT-based system for monitoring and regulating temperature. The results of the study show that this tool can detect and stabilize water temperature automatically based on the measured temperature level, provide real-time information, and facilitate the process of monitoring pond water temperature.